2022
DOI: 10.1038/s41598-022-16914-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of binding interactions of SARS-CoV-2 spike protein and DNA-peptide nanostructures

Abstract: Binding interactions of the spike proteins of the severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) to a peptide fragment derived from the human angiotensin converting enzyme 2 (hACE2) receptor are investigated. The peptide is employed as capture moiety in enzyme linked immunosorbent assays (ELISA) and quantitative binding interaction measurements that are based on fluorescence proximity sensing (switchSENSE). In both techniques, the peptide is presented on an oligovalent DNA nanostructure, in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Fortunately, His-tagged Ace2 did provide good binding curves with a K D of 4.25 ± 1.52 nM (over 6 runs performed during the 3 days of assay measurements, see Supporting Information Section 4.3.2). This is stronger binding than previous measurements performed by Surface Plasmon Resonance 76 that showed 94.6 ± 6.5 nM for (monomeric) SARS-CoV-2-S1, but can be explained by multivalency of the trimer as shown by Kruse et al 77 . All 152 compounds were first analyzed using 8-point dilution series between 50 nM and 100 µM concentrations, revealing 7 compounds to be potential binders.…”
Section: Binding Assays To N Rdrp (Nsp12 Domain) Scontrasting
confidence: 61%
“…Fortunately, His-tagged Ace2 did provide good binding curves with a K D of 4.25 ± 1.52 nM (over 6 runs performed during the 3 days of assay measurements, see Supporting Information Section 4.3.2). This is stronger binding than previous measurements performed by Surface Plasmon Resonance 76 that showed 94.6 ± 6.5 nM for (monomeric) SARS-CoV-2-S1, but can be explained by multivalency of the trimer as shown by Kruse et al 77 . All 152 compounds were first analyzed using 8-point dilution series between 50 nM and 100 µM concentrations, revealing 7 compounds to be potential binders.…”
Section: Binding Assays To N Rdrp (Nsp12 Domain) Scontrasting
confidence: 61%
“…Fortunately, His-tagged Ace2 did provide good binding curves with a K D of 4.25 � 1.52 nM (over 6 runs performed during the 3 days of assay measurements, see Supporting Information Section 4.2.3). This is stronger binding than previous measurements performed by Surface Plasmon Resonance [90] that showed 94.6 � 6.5 nM for (monomeric) SARS-CoV-2-S1, but can be explained by multivalency of the trimer as shown by Kruse et al [91]. All 152 compounds were first analyzed using 8point dilution series between 50 nM and 100 μM concentrations, revealing 7 compounds to be potential binders.…”
Section: Nsp5 Protease Cleavage Assays In Cellsmentioning
confidence: 63%
“…Compared to the conjugation of only one SBP1-peptide per DNA nanostructure, the affinity to recombinantly produced, full-length spike protein homotrimers was significantly enhanced for three SBP1-peptides per nanostructure. 126 More recently, Issmail et al demonstrated that the above-mentioned concept is also applicable for respiratory syncytial viruses (RSV). 128 Notably, while the previously described studies focused on binding of the peptide-DNA structures to viral proteins or whole viruses, this study showed that the structures are also capable of acting as an effective RSV entry inhibitor in vitro .…”
Section: Templated Interactions With Biological Systemsmentioning
confidence: 99%
“…Two recent publications by Kruse et al utilized fluorescence proximity sensing, a technology called switchSENSE 124 to investigate the binding of peptide-decorated DNA trimeric structures to influenza A virus (IAV) 125 and severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). 126 For IAV, the peptide PeB was used, which has been designed to interfere with the function of IAV's Hemagglutinin (HA) protein. It was observed that three PeB peptides linked to DNA structures showed oligovalent binding to different strains of IAV.…”
Section: Templated Stimulation Of In Vitro and In Vivo Pathwaysmentioning
confidence: 99%